Pengaruh Gaya Kepemimpinan Transformasional, Pengalaman Kerja Dan Lingkungan Kerja Terhadap Peningkatan Kinerja Karyawan Pada PT. Bank Tabungan Negara (BTN) Medan - Chairunnisa, T.Lyza Tahura; Fahlevi, Alvin; Rahma, Raihana Firjatullah (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research was conducted at PT. Bank Tabungan Negara (BTN) Medan with the research objective of analyzing the influenced of transformational leadership style, work experience and work environment on improving employee performance. The population were employees who work at PT. Medan State Savings Bank (BTN) was 110, sampling was taken using boring sample so that the total research sample was 110 respondents. Data analysis techniques use multiple linear regression, classical assumption testing and hypothesis testing, Based on the results, it showed that transformational leadership style, work experience and work environment partially and simultaneously have a significant effect on improving employee performance in the company. There was strong correlation between transformational leadership style, work experience and work environment on employee performance and the percentage of employee performance at PT. Bank BTN Medan could explained by transformational leadership style, work experience and work environment by 47.90% and the remaining 52.1% could explained by other variables not studied.